2012
DOI: 10.1039/c2jm32000b
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and conducting ITO thin films by spin coating of an aqueous precursor solution

Abstract: An environmentally friendly aqueous sol-gel process has been developed to fabricate thin films of indium tin oxide (ITO). A stable sol was prepared from indium nitrate and tin acetate precursors together with acetic acid and ethylene glycol. The sol transformed into an amorphous gel during heating, which decomposed and crystallized further to nano-crystalline ITO at $300 C. The nanocrystalline ITO powders prepared from the precursor gel were homogeneous and single phase with particle sizes around 15 nm. The aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 40 publications
2
72
1
Order By: Relevance
“…By this polymer-complex solution method, less amount of organics is used and for the synthesis of CaAl2O4 a phase pure material was prepared with a higher amount of cations than the number of functional groups in the polymer (Gülgün et al 1999) For some specific cations it has more recently been observed that complexing agents with -OH groups like ethylene glycol and polyvinyl alcohol (PVA) are better compounds to promote homogeneity of the final oxide than carboxylic acids. This has empirically been found to be of great advantage for amphoteric cations like In 3+ , Sn 4+ and Bi 3+ in the preparation of indium tin oxide (Kundu and Biswas 2008;Sunde et al 2012) and BiFeO3 (Selbach et al 2007;Liu et al 2010). An amino carboxylic acid, e.g.…”
Section: What Is the Modified Pechini Synthesis?mentioning
confidence: 99%
See 4 more Smart Citations
“…By this polymer-complex solution method, less amount of organics is used and for the synthesis of CaAl2O4 a phase pure material was prepared with a higher amount of cations than the number of functional groups in the polymer (Gülgün et al 1999) For some specific cations it has more recently been observed that complexing agents with -OH groups like ethylene glycol and polyvinyl alcohol (PVA) are better compounds to promote homogeneity of the final oxide than carboxylic acids. This has empirically been found to be of great advantage for amphoteric cations like In 3+ , Sn 4+ and Bi 3+ in the preparation of indium tin oxide (Kundu and Biswas 2008;Sunde et al 2012) and BiFeO3 (Selbach et al 2007;Liu et al 2010). An amino carboxylic acid, e.g.…”
Section: What Is the Modified Pechini Synthesis?mentioning
confidence: 99%
“…This is an interesting aspect with this synthesis approach. Upon further heating the metastable phase will be transformed to the thermodynamically stable phase (Schumm et al 2011;Sunde et al 2012). During preparation of oxides with very basic cations, the formation of intermediate carbonates might occur due to the availability of CO2 from the decomposition of the organics.…”
Section: What Is the Modified Pechini Synthesis?mentioning
confidence: 99%
See 3 more Smart Citations